The Correlational Study Between Speaking Ability and English Learning Motivation - -, Luvita Saputri (International Journal of Research in Education, 2025)
The aim of this research is to examine the relationship between motivation and speaking ability among students at Universitas Teknokrat Indonesia. This study employs a quantitative method, utilizing a Likert scale questionnaire comprising 20 questions to measure both instrumental and integrative motivation. Data were collected from a sample of 36 students. The data were analyzed using correlation analysis to determine the relationship between motivation and speaking ability. The findings indicate a significant positive correlation between motivation and speaking ability. Students with higher motivation tend to exhibit better speaking skills, which, in turn, fosters greater confidence in English communication. The study highlights the importance of motivation in enhancing communicative competence and suggests that integrating motivational strategies into teaching practices can improve students' English-speaking abilities. Overall, this research underscores the critical role of motivation in advancing language skills among English majors at Universitas Teknokrat Indonesia.